Corruption risks and schemes in public procurement procedures within the modern digital environment - Kovalenko, Mykola; Karamyshev, Dmytro (Theory and Practice of Public Administration, 2025)
This article examines the transformation of corruption risks within the public procurement sector amidst the operation of Ukraine’s contemporary digital infrastructure. Particular emphasis is placed on a contradictory contemporary trend: notwithstanding the strategic drive toward absolute transparency and the deployment of advanced digital tools (Prozorro, DREAM, risk-oriented monitoring modules), corruption levels have not diminished but rather evolved into novel, latent forms. Corruption is emerging as a dynamic phenomenon that successfully adapts to digitalization by shifting the center of gravity from overt procedural violations to domains inaccessible to automated control, specifically targeting the stages of planning, direct contracting, and the physical execution of contracts. The methodological framework of the study is constituted by a synthesis of systemic, institutional, and comparative approaches, which facilitated the examination of public procurement as a holistic system susceptible to destructive influences throughout various stages of its implementation. The informational and empirical basis of the research comprises Ukrainian regulatory legal acts, analytical reports from the National Agency on Corruption Prevention, case law from the High Anti-Corruption Court, and studies by Transparency International Ukraine covering the 2024–2025 period. The article provides a detailed analysis of the domestic infrastructure of digital tools (Prozorro, BI Prozorro, DOZORRO, Clarity Project, YouControl, Spending, DREAM). It is argued that while the existing toolkit ensures a high degree of transparency for external monitoring, it does not constitute a sufficient condition for eliminating malpractices occurring outside the electronic system. A key outcome of the work is the development of a systematized classification of corruption risks and their implementation schemes across the stages of the procurement cycle. Specifically, at the planning stage, schemes involving the manipulation of expected value and the artificial division of the procurement subject to evade open tenders were identified, while at the documentation preparation stage, mechanisms for tailoring technical requirements to a specific manufacturer and establishing discriminatory qualification criteria were revealed. In the context of martial law, particular attention is devoted to abuses related to direct contracting through the interpretation of “urgent need” and the involvement of shell companies. Simultaneously, at the contract execution stage, identified as the most critical, schemes involving unjustified price increases via supplementary agreements, the substitution of goods with lower-quality alternatives, and the signing of acceptance certificates for fictitious works were analyzed. Based on the conducted analysis, the necessity of shifting the anti-corruption policy strategy is substantiated: transitioning from exclusively external oversight to the development of an effective internal control system. The implementation of the “Three Lines of Defense” model at the level of procuring entities is recommended, which envisages a clear delineation of functions between risk owners (operational level), control units (compliance), and internal audit. It is concluded that overcoming corruption requires not merely the automation of processes, but profound changes in societal values and the system of economic relations.